Determination of the horizontal projection parameters of tree crown by means of the UAV-survey materials - Bidolakh, D. I.; Bilous, A. M.; Kuziovych, V. S. (Forestry and Forest Melioration, 2019)
Introduction Current trends in forestry and park research lead to the transition to a new level of ways of obtaining forest mensuration indicators by means of modern tools, computer technologies, remote sensing methods, global positioning devices, etc. Materials and Methods The aim of the study was to develop a new approach to measuring projection of crowns of trees and shrubs in order to eliminate a need in linear measurements, increase the speed of operation and ensure greater reliability of the data on a shape of the crown. For this purpose, we have proposed the use of aerial photography of the area from an unmanned aerial vehicle (to obtain current and inexpensive shooting material) with the subsequent determination of a configuration of the crown projection as well as to obtain the data on its size by the orthophotoplan processed in the environment of the geographic information system. The proposed method was tested in forest and garden plantations of the town of Berezhany in Ternopil Region (Ukraine) by comparing the results of this approach with the traditional method which includes a usage of a measuring tape for determining the radii of the crown in eight directions. It enabled comparing the results of different measurement approaches applied in a traditional way with the usage of UAV surveys in GIS QGis 3 according to linear measurements and calculating control radii. Results The findings show that the processing of UAV-shooting materials in GIS makes it possible to simplify obtaining data on configuration of the crown horizontal projection, to improve the measurement quality of its area and to find out a real contour of the projection perimeter. As a result, it is found that the proposed method allows obtaining results of high accuracy (with deviation up to 3%) due to clearer understanding and more precise definition of crown configurations. Thus, this approach, by means of the usage of GIS tools, allows determining dimensions and configuration of horizontal projections of crowns of trees and shrubs minimising at that time-consuming field work. Creation of a research database makes it possible to store both the measurements data and photographs of studied objects in digital form. The proposed approach has two disadvantages. The first one is the fact that it is hard to implement it in a dense forest stand (where it is not always possible to accurately assess the parameters of the crown by individual trees). The second one is a need for well-trained users. Conclusions This approach can be used to manage forests and parks, namely, to study the interaction of woody plants in a stand, to determine the stand’s density, to take an inventory of greenery, to analyse the balance and landscape features of the territory and to plan work and other scientific research. The use of modern tools helps store the spatial and attributive data in digital form and enables its sorting, creating of special queries and statistical analyses, preparing of cartographic documentation and data visualization. 2 Figs., 1 Table, 16 Refs.